Academic Stress, Family Environment and Music at Adolescent Stage: Exploring the impact of music and family environment on academic stress in adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The relationship between music and reduction in other forms of stress, especially academic stress among adolescents, remains unclear by many types of research on the stress levels. The present study was descriptive in nature. For the current study, the survey method was used. The difference in Academic stress and Family environment of music and non-music students were studied. The data was also used to find out the relationship between academic stress and family environment variables. The purpose of this research is to see the relationship between family environment and academic stress among music and non-music students. In the present study, the sample was comprised of 100 students including 50 boys (25 music students and 25 non-music students) and 50 girls (25 music students and 25 non-music students) of government schools of Chandigarh. In order to see the Academic stress and family environment of XI class adolescents of Chandigarh. For analyzing the data correlation and t-test was used. The results revealed there is a negative correlation between Academic stress and Family Environment. So it can be said that the family environment has a significant relationship with academic stress. On the other hand, there is a significant difference between music and non-music students as well as among boys and girls at the stage of an adolescent on the variable Academic stress.